2022
DOI: 10.1364/ome.459938
|View full text |Cite
|
Sign up to set email alerts
|

Modeling optical constants from the absorption of organic thin films using a modified Lorentz oscillator model

Abstract: Optical constants of organic thin films can be evaluated using the Lorentz oscillator model (LOM) which fails to fit inhomogeneously broadened absorption of highly concentrated molecular films. In modified LOM (MLOM), the inhomogeneous broadening is implemented through a frequency-dependent adjustable broadening function. In this work, we evaluate the optical constants of rhodamine 6G doped poly-vinyl alcohol thin films with varying doping concentration (including also extensively high concentrations) using ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…87 Instead, this overall rate enhancement effect can be understood as arising from a cavity-induced renormalization of the photonic density of states, as was recently inferred for different reactions. 56,88 This effect does not require strong light-matter coupling. Nevertheless, our results indicate that enhanced absorption at the LP branch followed by conversion of LPs into dark states does enable more efficient use of photons resonant with the LP branch compared to that outside the cavity.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…87 Instead, this overall rate enhancement effect can be understood as arising from a cavity-induced renormalization of the photonic density of states, as was recently inferred for different reactions. 56,88 This effect does not require strong light-matter coupling. Nevertheless, our results indicate that enhanced absorption at the LP branch followed by conversion of LPs into dark states does enable more efficient use of photons resonant with the LP branch compared to that outside the cavity.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Multiple studies have shown that relaxation dynamics in molecular polaritons are dominated by dark states. ,, Indeed, excitation into any state (UP, LP, or dark states) tends to localize both spatially and energetically into the dark state manifold because of the latter’s large density of states. ,,, This aspect is particularly relevant in molecular polaritons with large disorder, since the latter ensures energetic overlap between polariton branches and molecular states over a large range of detunings. , The trend we observe in γ (Figure d) can be rationalized within this context and suggests that photochemistry in our systems is principally driven by (relatively) localized dark states: as the detuning between the excitation and bare exciton resonance increases, we expect a smaller LP → dark state transfer rate. ,, The other decay pathway for LPs is to the ground state, typically on sub-100 fs time scales, dictated primarily by cavity losses. Given this kinetic competition between polariton localization into dark states and polariton decay to the ground state, large detuning (small LP → dark state rate) results in a lower dark state yield and thus lower photochemical yields (Figure d).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations